Estudo teórico de dopagem substitucional de carbono em monocamada de fosforeno - Pedrosa, Renan Narciso (2019)
In this work, we have explored the structural and electronic properties and energy stability of substitutional carbon impurities in a phosphorene monolayer through the first principles calculations based on the Density Functional Theory (DFT). Carbon defects were investigated in the phosphorene monolayer for various structural configurations and impurity concentrations. Among them, the defects in carbon lines in the zig-zag and armchair direction. Ours results finding that for all different doping configurations considered herein, the defects formation is ruled by exothermic processes. In addition, for the most stable energetic configurations we have obtained values of 2.35 eV/atom and 2.36 eV/atom. Furthermore, the presence of the substitutional carbon impurity in the phosphorene monolayer gives rise to fluctuations in charge density. The Carbon defects behave as acceptor impurities, receiving charges of the neighboring phosphorus atoms, thus resulting in a p-type doping. In addition, it was verified that the presence of the impurity in the phosphorene sheet, for some configurations, induced the direct gap transition from the phosphorene monolayer to the indirect gap and for other configurations, the metallic character was observed.